Discovering genomics, proteomics, and bioinformatics - Campbell, A. Malcolm (Pearson Benjamin Cummings, 2007)
Discovering Genomics is the first genomics text that combines web activities and case studies with a problem-solving approach to teach upper-level undergraduates and first-year graduate students the fundamentals of genomic analysis. More of a workbook than a traditional text, Discovering Genomics, Second Edition allows students to work with real genomic data in solving problems and provides the user with an active learning experience." "The Second Edition has been thoroughly revised and updated to incorporate the latest scientific findings on popular topics such as disease-causing organisms and genetic defects. Case study chapters have been placed throughout the book to tie real-life scenarios into the concepts that follow. Two of the book's key pedagogical features, Discovery Questions and Math Minutes, have also been updated and expanded." "The interactive companion website has been reprogrammed with JMOL, the latest 3-D software used to view DNA structures.